Characterization of Food Amyloid Protein Digestion by Conical Nanopore. Issue 11 (8th March 2020) - Giamblanco, Nicoletta; Janot, Jean‐Marc; Gubbiotti, Alberto; Chinappi, Mauro; Balme, Sebastien
Abstract: β‐lactoglobulin aggregates are used as structuring agents in food processing. Their enzymatic degradation follows different pathways depending on the enzyme and the pH. The transient species produced during the degradation process are difficult to characterize under continuous measurement. Here, conical track‐etched nanopores are used to investigate the β‐lactoglobulin degradation by pepsin (pH 2) and trypsin (pH 9). Before enzyme addition, two distinct populations, oligomers and protofibrils, are identified. Just after enzyme addition, the aggregate size decreases. For pepsin, a phenomenon of reaggregation that does not occur for the trypsin is evidenced. In addition, after 140 min a larger population of aggregate appears. The experimental results are supported by a kinetic model. This work also demonstrates that conical nanopore allows following the kinetic of transient protein aggregate intermediates during enzymatic degradation. Abstract : Here, conical track‐etched nanopores are used to investigate the β‐lactoglobulin degradation by pepsin (pH 2) and trypsin (pH 9). Before enzyme addition, two distinct populations, oligomers and protofibrils, are identified. Just after enzyme addition, the aggregate size decreases. For pepsin, a phenomenon of reaggregation that does not occur for the trypsin is evidenced.